Neutral taxation of shareholder income?: corporate responses to an announced dividend tax - Annette Alstadsæter; Erik Fjaerli (Center for Economic Studies and ifo Institute (CESifo), 2009)
The introduction of the 2006 Norwegian shareholder income tax was announced in advance, and it increased top marginal tax rates on individual dividend income from zero to 28 percent. We document strong timing effects on dividend payout on a large panel of non-listed corporations, with a surge of dividends prior to 2006 and a sharp drop after. Mature firms are more likely to pay dividends, and high asset growth increases the probability of retaining all earnings. Intertemporal income shifting through the timing of dividends seems to be a drain on internal equity and cause increases in the corporations' debt-equity ratios. The debt ratios drop sharply after the implementation of the reform.
Keywords: G32; G35; H24; H25; 330; Neutral dividend tax; dual income tax; intertemporal income shifting; anticipation effects; corporate financial policy; transition; Dividende; Kapitalertragsteuer; Ankündigungseffekt; Unternehmensfinanzierung; Kapitalstruktur; Duale Einkommensteuer; Besteuerungsgrundsatz; Norwegen